2022
DOI: 10.3324/haematol.2021.279739
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF3 modulates hematopoietic stem cells by recognizing RNA m<sup>6</sup>A modification on <i>Ccnd1</i>

Abstract: Hematopoietic stem cells (HSCs) build up the blood system throughout lifespan. N6-methyladenosine (m6A), the most prevalent RNA modification, modulates gene expression via the processes of “writing” and “reading”. Recent studies showed that m6A “writer” genes (Mettl3 and Mettl14) play an essential role in HSCs. However, which reader deciphers the m6A modification to modulate HSCs remains unknown. In this study, we observed that dysfunction of Ythdf3 and Ccnd1 severely impaired the reconstitution capacity of HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…6 D ). Studies showed that EIF3 ( 45 ), YTHDF1 ( 47 , 48 ), YTHDF2 ( 46 ) and YTHDF3 ( 49 , 50 ) can serve as m 6 A readers that enhance the translation efficiency of m 6 A-modified mRNAs. Using siRNA screening ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 D ). Studies showed that EIF3 ( 45 ), YTHDF1 ( 47 , 48 ), YTHDF2 ( 46 ) and YTHDF3 ( 49 , 50 ) can serve as m 6 A readers that enhance the translation efficiency of m 6 A-modified mRNAs. Using siRNA screening ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that IGF2BP1 enhanced mRNA stability by recruiting PABPC1 to the target mRNA 35 . YTHDF3 was additionally proven to bind PABPC1 in haematopoietic cells and enhance Ccnd1 translation 36 . PABPC1 was able to stabilize lncRNA‐PAGBC in gallbladder cancer, and activates the AKT/mTOR pathway to promote tumour growth and metastasis 37 .…”
Section: Discussionmentioning
confidence: 98%
“…YTHDF3 is also involved in the regulation of HSCs. YTHDF3 binds m 6 A on the 5’UTR of CCND1 mRNA and cooperates with PABPC1 and EIF4G2 to promote the expression of CCND1, a positive regulator of HSCs reconstitution capacity ( 87 ). While YTHDF3 facilitates the translation of FOXM1 and ASXL1 transcripts and is critical for maintaining HSC properties under stress conditions ( 88 ).…”
Section: The Roles Of the Ythdf Family In Physiological And Pathologi...mentioning
confidence: 99%
“…At present, many experiments have successfully constructed the YTHDF1/2/3 genetic KO mouse model using different techniques. First, the whole-body YTHDF1/2/3 KO mice are generated directly based on CRISPR/Cas9 by deleting a certain exon or inducing the premature appearance of a stop codon ( 87 , 88 , 110 , 213 ). Second, the Cre/LoxP technique is used to generate cell-specific conditional YTHDF1/2/3 KO mice ( 74 , 84 , 108 , 165 , 167 , 174 , 227 , 289 ).…”
Section: Limitations and Perspectivesmentioning
confidence: 99%